Financial Literacy and Digital Financial Behavior on Financial Decision Making - Alfiana; Upik Djaniar; Rezario Febrianta Chandra; Musran Munizu; Listiana Sri Mulatsih (Indonesian Journal Economic Review (IJER), 2026)
The purpose of this study is to understand how financial literacy and digital financial behavior influence financial decision making in the digital economy era. The research approach used in this study is descriptive research based on the analysis of theoretical relationships. To assist this research approach in explaining theoretical relationships, secondary data such as books, journals, and other related sources are needed. The results of this study indicate that the interaction between financial literacy and digital financial behavior is the two main pillars that determine the quality of financial decision making in the digital economy era. The interplay between financial literacy, digital financial behavior, and financial decision making creates a crucial synergy in navigating today's economic complexities. Financial literacy and digital financial behavior serve as cognitive foundations, while financial decision making is the manifestation of actions within the technology ecosystem.